2017
DOI: 10.21082/bullittro.v28n1.2017.75-88
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF ESSENTIAL OIL MIXTURES ON MORTALITIES AND OVIPOSITION DETERRENTS OF Crocidolomia pavonana AND Helopeltis antoniierrents Of Crocidolomia Pavonana And Helopeltis Antonii

Abstract: Essential oil, such as citronella, lemongrass, ageratum, and clove are known to be toxic and repel certain pests. Mixing two or more essential oils are expected increasing their insecticidal properties. The experiments aimed to examine the effect of essential oils mixtures (EOs) on mortalities and oviposition deterrents of Crocidolomia pavonana and Helopeltis antonii. The experiments were conducted at the laboratory and green house of the Indonesian Spices and Medicinal Crops Research Institute. The tested mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Meanwhile, the inert solution signified no effect on oviposition deterrent as indicated by the numbers of eggs laid which were not significant from control. Mardiningsih and Balfas (2017) also reported the highest effective repellency (63.30 %) of citronella and clove oils mixture in alkyl glycerol ftalat to H. antonii.…”
Section: Oviposition Deterrent and Mortality Of H Antonii Adultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Meanwhile, the inert solution signified no effect on oviposition deterrent as indicated by the numbers of eggs laid which were not significant from control. Mardiningsih and Balfas (2017) also reported the highest effective repellency (63.30 %) of citronella and clove oils mixture in alkyl glycerol ftalat to H. antonii.…”
Section: Oviposition Deterrent and Mortality Of H Antonii Adultsmentioning
confidence: 86%
“…Previous study revealed that mixtures of citronella + clove oils, lemongrass + clove oils, ageratum + clove oils in various ratios were two to three times more toxic and had higher oviposition deterrent effect than individual EOs on Crocidolomia pavonana and H. antonii. Citronella + clove oils and lemongrass + clove oils at the ratio of 1:1 showed the lowest number of eggs laid by C. pavonana and H. antonii (Mardiningsih and Balfas 2017). Those mixtures are in Emulsifiable Concentrate (EC) formulation.…”
Section: Introductionmentioning
confidence: 99%